The Effect of Pictures Media on Sentence Writing Skills of 7th Graders - Rara Dewi Putri Rahmadani; Armeria Wijaya; Listya Dewi Damajanti (PROCEEDING UMSURABAYA, 2026)
This classroom action research aimed to determine the effectiveness of picture media in improving the simple English sentence writing skills of seventh-grade students at a junior high school in Surabaya, Indonesia. The research, conducted in two cycles, utilized pre-tests, post-tests, observations, and open-ended questionnaires to collect quantitative and qualitative data. Initial findings from the pre-test indicated that the majority of students had difficulty constructing basic English sentences, with an average score of 69.03 and only 57.69% achieving the minimum passing criteria. Cycle I, which integrated picture media as a visual stimulus, showed a significant improvement, with the average post-test score increasing to 89.80 and learning mastery rising to 88.46%. However, Cycle II showed a slight decrease in the average post-test score to 87.88, although learning mastery remained the same. Qualitative data from the questionnaires indicated that grammatical challenges, a less conducive learning environment, and decreased student motivation contributed to this slight decline. While the use of picture media was initially proven beneficial in enhancing students' ability to produce simple sentences by providing context and stimulating ideas, this research highlights the need for a multi-faceted approach in teaching writing. This includes addressing grammatical understanding, managing classroom dynamics, and sustaining student engagement to achieve more consistent and significant improvements in writing skills.